Factors Affecting Dividend Policy (Case Study of Manufacturing Companies Listed on the IDX 2015-2019) - Fathihani, Fathihani; Solihin, Agung (Dinasti Publisher, 2024)
This research aims to estimate and analyze the impact of internal company factors on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The internal factors that determine dividend policy tested in this research are Current Ratio (CR), Debt-to-Equity Ratio (DER), Asset Growth (Growth), Collateralizable Assets (COL), and Return on Equity (ROE), while policy Dividends are proxied by the Dividend Payout Ratio (DPR. The population in this study is 188 manufacturing companies registered on the IDX for the 2015-2019 period. The sampling technique used is purposive sampling, which is based on the suitability of the sample characteristics with predetermined sample selection criteria in order to obtain The research sample is 24 companies. The type of data used in this research is secondary data obtained from the official website of the Indonesia Stock Exchange (BEI). The data analysis method uses descriptive analysis and panel data regression models. Debt-to-Equity Ratio (DER), Asset Growth (Growth) have no effect on the Dividend Payout Ratio (DPR). Meanwhile, the Collateralizable Assets (COL) and Return on Equity (ROE) ratios have an effect on the Dividend Payout Ratio (DPR).